Diagnosing the Causes of Failure in the Construction Sector Using Root Cause Analysis Technique - Faiq M. S. Al-Zwainy; Ibrahim A. Mohammed; Ibrahim F. Varouqa (Journal of Engineering)
The aim of this study is identifying and diagnosing the causes of construction project failure by using different project management process groups. These groups were initiation process group, planning process group, design process group, contract process group, executing and monitoring process group, and close process group. Also, the relative importance of the causes of construction project failure was investigated. Three techniques were used in this study: Ishikawa diagrams, Pareto diagrams, and 5-why techniques. The results were generally identified and diagnosed thirty-five causes of the construction project failure; however, only twenty-three of the causes were the most important. The majority of causes (thirteen causes) were obtained by using executing and monitoring project management process group. Seven causes were obtained by using contract project management process group. In addition, fewer causes (only three causes) were obtained by using initiation project management process group.